2019
DOI: 10.1080/2331186x.2019.1567895
|View full text |Cite
|
Sign up to set email alerts
|

Exploring gender differences in achievement through student voice: Critical insights and analyses

Abstract: The superior performance of females over males at high school and other levels appears to be a growing international phenomenon. This is notwithstanding the fact that a recent and significant comprehensive global meta-analysis that examined male-female performance at all levels revealed that girls have always outperformed boys in school. This meta-analysis included 502 effect sizes from 369 independent samples from articles published over a 100-year period beginning in 1914 with participants totaling 538,710 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 19 publications
4
14
1
2
Order By: Relevance
“…The ndings of the present study are consistent with those of a study that assessed KAP of hygiene among students in Ethiopia, where 48% of the students had poor knowledge related to hygiene and sanitation; the nding was associated with the illiteracy levels of parents and poor socioeconomic backgrounds [27]. Studies conducted in resource-poor settings exhibited that communities face nancial challenges regarding hardware installation (latrines/toilets), whereas others still lack the basic understanding of using a toilet to defecate due to cultural norms [25,[27][28][29][30][31][32]. Students' knowledge regarding the signi cance of maintaining a clean house and hand washing was comparable to that observed in studies conducted in Kenya and Turkey, which indicated that students are aware of the signi cance of such practices and possess moderate knowledge on the importance of handwashing [15,33].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The ndings of the present study are consistent with those of a study that assessed KAP of hygiene among students in Ethiopia, where 48% of the students had poor knowledge related to hygiene and sanitation; the nding was associated with the illiteracy levels of parents and poor socioeconomic backgrounds [27]. Studies conducted in resource-poor settings exhibited that communities face nancial challenges regarding hardware installation (latrines/toilets), whereas others still lack the basic understanding of using a toilet to defecate due to cultural norms [25,[27][28][29][30][31][32]. Students' knowledge regarding the signi cance of maintaining a clean house and hand washing was comparable to that observed in studies conducted in Kenya and Turkey, which indicated that students are aware of the signi cance of such practices and possess moderate knowledge on the importance of handwashing [15,33].…”
Section: Discussionsupporting
confidence: 90%
“…Findings suggest that girls may require additional training to improve their knowledge. However, evidence from various international contexts suggests a clear gender gap in academic achievement, with boys lagging behind [27]. Furthermore, students from urban areas outperformed those from rural areas.…”
Section: Discussionmentioning
confidence: 99%
“…Aun cuando está empíricamente documentado que la brecha de género -entendida aquí como diferencias hombre-mujer-en las puntuaciones obtenidas en pruebas puede variar apreciablemente entre países (Jackman et al, 2019), nuestros hallazgos empíricos alinean a España con el comportamiento promedio de los países de la OCDE. El valor relativamente pequeño de la brecha de género observado, una vez controlado el efecto del ISEC, se reduce a una diferencia no significativa cuando se prescinde de ese efecto y se toman en consideración los datos más recientes del rendimiento en Ciencias correspondientes a la edición de 2018 (Ministerio de Educación y Formación profesional, 2019).…”
Section: Discussionunclassified
“…A recent meta-analysis confirmed that the wider literature reports similar findings [ 66 ], and yet, our regression analysis failed to show gender as a predictor of academic scores. As other authors argue, genders are more alike than different [ 67 ], and socioeconomic status, stereotype manipulation and school-related factors may explain most of the academic differences [ 68 ].…”
Section: Discussionmentioning
confidence: 99%